2022
DOI: 10.1038/s41598-022-22210-3
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors based on novel nonlinear delta-function photonic crystals comprising weak nonlinearities

Abstract: In this research, we propose a novel nonlinear delta-function photonic crystal for detecting sodium iodide (NaI) solution of different concentrations. The suggested structure comprises 50 delta stacks of GaP in an aqueous solution of NaI. These stacks are considered to have weak defocusing nonlinearity in the order of 10−6 (V/m)−2. Due to nonlinearity of the design, a defect-like resonance is formed within the photonic band gap. Thus, the detection of NaI with different concentrations can be easily investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A temperature and magnetic field detecting sensor based on photonic crystal fiber based structure with high sensitivity [34,35]. Mehaney et al proposed a sodium iodide detecting photonic crystal biosensor [36]. Taha and coauthors presented numerous sensors for heavy metals detection in water [37], and sodium iodide detection [38], and isoprene in exhaled breath [39].…”
Section: Introductionmentioning
confidence: 99%
“…A temperature and magnetic field detecting sensor based on photonic crystal fiber based structure with high sensitivity [34,35]. Mehaney et al proposed a sodium iodide detecting photonic crystal biosensor [36]. Taha and coauthors presented numerous sensors for heavy metals detection in water [37], and sodium iodide detection [38], and isoprene in exhaled breath [39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are the important structures for controlling the propagation of light and sensing applications 26 , 27 . Recently, the propagation of electromagnetic waves through photonic crystals, especially photonic crystals based on the 2D materials, has been widely investigated both theoretically and experimentally by researchers and significant results have been obtained 28 50 . The optical absorbance of graphene on the one-dimensional photonic crystal has been investigated theoretically by Liu et al 28 The authors showed that, when graphene is placed on the photonic crystal, its absorbance coefficient increases greatly.…”
Section: Introductionmentioning
confidence: 99%